Setting the Table: Trauma-Informed Groupwork in Challenging Times - Gherardi, Stacy A; Gurrola, Maria; Tafoya, Joshua; Garling-Spychala, Bethany (Groupwork, 2019)
Political developments across the globe have created circumstances in which many feel increasingly threatened by forces of political oppression. These forces have been especially pronounced for communities of color and immigrant communities in the United States in the last several years, creating a context that is ripe for the restorative and transformative potential of groupwork. In this paper, we describe our experiences as social work faculty in a university community Southwestern United States as we sought to implement a year-long groupwork initiative following the 2016 elections. Utilizing an open and self-directed approach, these inclusive dialogues were intended to provide opportunities for mutual understanding and collective action. Participant feedback suggested that they were largely positive experiences; however, attendance and deep engagement were continual challenges. In reflecting on these experiences we conclude that deeper attention to the concept of political trauma and a more explicitly trauma-informed approach to group planning, formation, and engagement could have supported our efforts. In response, we propose a framework which integrates the Sanctuary model of trauma-informed care with a pedagogy of political trauma as a means of conceptualizing trauma-informed groupwork in response to political oppression.